The origin of humankind - Leakey, Richard E. (New York : Basic Books, 1994)
Richard Leakey examines the evidence and the various theories about the origin of human beings.
Includes bibliographical references (p. 159-164) and index.
Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Adult
Keywords: Fossil hominids; Human evolution; Fossil hominids; Human origins